Assessing Factors Impacting Taxpayer Compliance in Medan City: Awareness, Sanctions, and E-Samsat Implementation - Leni, Tiara; Masyitah, Emi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Compliance with motor vehicle taxpayers has decreased during the Covid-19 period and has increased again at the beginning of 2022. Awareness of motor vehicle taxpayers is still low, which can be seen from the number of motor vehicles which is not balanced with the number of people paying taxes each year. The tax sanction enforcements that have been implemented by the Medan city government are still not very effective, where there are still several people who violate tax sanction enforcements. The implementation of E-Samsat is optimal, it’s just that there needs to be an even dissemination of information about E-Samsat considering that there are still people who don’t know what E-Samsat is. This research aims to determine and analyze the influence of taxpayer awareness, tax sanction enforcements and the implementation of E-Samsat on motor vehicle taxpayer compliance in Medan City Samsat. This research uses primary data where the data collection technique in this research was carried out using a questionnaire distributed to respondents with a population of 232,529 taxpayers with a sample size of 100 respondents. From the results of the analysis obtained from this research, it is known that the results of the t test on taxpayer awareness, tax sanction enforcements and the application of E-Samsat have a partially positive and significant effect on taxpayer compliance with a calculated t value > t table, and for the F test it can be seen from the value the. F count > F table and the significance value is 0.000 < α= 0.05, which means that the variables of taxpayer awareness, tax sanction enforcements and implementation of E-Samsat simultaneously have a positive and significant effect on taxpayer compliance.